Essential Kummer’s vectors - Uher, Zbyněk (Annales Mathematicae Silesianae, 2003)
In this paper Kummer's elements in the Stickelberger ideal of the group ring of the Galois group of the extension ℚ(ζ)/ℚ over the ring of rational integers are studied. A special linear operator is constructed for better understanding to these elements, and Kummer's elements are mapped to Kummer's vectors. Then one computational method is presented and the coherence between its results and the property of being essential for Kummer's vectors is shown.